An atypical cause of myocardial infarction: case report of an obstructing papillary fibroelastoma of the aortic valve. Issue 2 (5th May 2019) - Logan, Niamh; Islam, Mohammad Sirajul; Chughtai, Jehan Zeb; Murphy, Niamh F
Abstract: Background: Papillary fibroelastomas are rare primary cardiac tumours with a prevalence of 0.01% at autopsy. They are histologically benign tumours but have been demonstrated through case series to confer an increased risk of thrombo-embolism resulting in: transient ischaemic attack, stroke, myocardial infarction, and pulmonary and systemic embolization. Case summary: A 54-year-old woman presented with central chest pain radiating to her left arm. At presentation there was a significant troponin rise; initial high-sensitivity troponin-I (hsTn-I) 660 pg/mL increased to 3340 pg/mL at 6 h. Coronary angiogram did not reveal any obstructing coronary artery disease. Echocardiography revealed a rounded, mobile mass on the left coronary cusp of the aortic valve suspicious for papillary fibroelastoma. The patient underwent shave excision of the lesion. Intra-operatively it was noted that the mass intermittently sat within the ostium of the left main resulting in its occlusion. Histology confirmed a papillary fibroelastoma. Discussion: Primary cardiac tumours are rare but can cause life-threatening complications such as stroke, myocardial infarction, and cardiac arrest. In the literature, the mechanism of these complications is mainly attributed to thrombo-embolism. This case demonstrates the utility of echocardiogram in investigating and diagnosing a rare cause of myocardial infarction and highlights an unusual mechanism, that is tumour causing obstruction of the coronary ostium.